Increased 28‐day mortality due to fluid overload prior to continuous renal replacement in sepsis associated acute kidney injury. Issue 2 (31st August 2021) - Fang, Junjun; Wang, Minjia; Gong, Shijin; Cui, Nannan; Xu, Liang
Abstract: Patients with sepsis are prone to fluid overload (FO) due to fluid resuscitation, irrespective of stage of acute kidney injury (AKI). The aim of our study was to analyze the association between FO at continuous renal replacement therapy (CRRT) initiation and 28‐day mortality in patients with sepsis associated AKI (S‐AKI). In this retrospective study, data for patient characteristics were collected and 28‐day mortality were studied. We also analyze association of variables, including FO degrees with 28‐day mortality. Earlier commencement of CRRT showed better outcome. Non‐survivors had higher FO than survivor (9.17% vs. 5.20%; p = 0.016). Survival in patients with FO > 10% over 28 days was significantly worse compared to those with FO ≤ 10% ( p = 0.006). Multivariate analysis showed, FO > 10% (95%CI [1.721, 17.195], p = 0.004) was significantly associated with increased 28‐day mortality. In S‐AKI requiring CRRT, FO > 10% at CRRT initiation was independently associated with 28‐day mortality.